Teachers as researchers : qualitative inquiry as a path to empowerment - Kincheloe, Joe L. (Rutledge education classic edition series, 2012)
"Teachers as Researchers urges teachers - as both producers and consumers of knowledge - to engage in the debate about educational research by undertaking meaningful research themselves. Teachers are being encouraged to carry out research in order to improve their effectiveness in the classroom, but this book suggests that they also reflect on and challenge the reductionist and technicist methods that promote a 'top down' system of education. It argues that only by engaging in complex, critical research will teachers rediscover their professional status, empower their practice in the classroom and improve the quality of education for their pupils. Now re-released to introduce this classic guide for teachers, the new edition of Teachers as Researchers now also includes an introductory chapter by Shirley R. Steinberg, McGill University, that sets the book within the context of both the subject and the historical perspective. In addition, she also provides information on some key writing that extends the bibliography of this influential book thereby bringing the material fully up to date with current research. Postgraduate students of education and experienced teachers will find much to inspire and encourage them in this definitive book" -- Provided by publisher